Pathogenic Bacteria - Kırmusaoğlu, Sahra; Bhonchal Bhardwaj, Sonia (IntechOpen, 2020)
Pathogenic bacteria are the main problem in hospital- and community-acquired infections. As bacteria continue to develop more resistance to antibiotics, it is imperative to develop antibacterial treatment strategies. Written by experts from all over the world, this book examines pathogenic bacteria and their link to multidrug resistance. Over thirteen chapters, it presents examples of pathogenesis, virulence factors, and treatment strategies.